2002
DOI: 10.1046/j.1365-4362.2002.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations of arsenicosis in two villages in Bangladesh

Abstract: The prevalence of arsenicosis was quite high and males were more vulnerable to arsenic contamination. Using skin manifestations, especially keratosis on the soles, as useful markers to detect and evaluate arsenicosis, it is clear that there is an urgent need to assess the exact prevalence and severity of arsenicosis in the population of Bangladesh in order to take measures to treat and control this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 12 publications
2
31
0
3
Order By: Relevance
“…The evidence for burden of disease of arsenic due to drinking groundwater is still very sparse and accumulating (Rahman et al 2009). Arsenic leads to non-cancerous (non-malignant) and cancerous (malignant) health effects including cardiovascular disease (National Research Council 2001;Lee et al 2005;Chen et al 2009;Rahman et al 2009), peripheral neuropathy , decreased intellectual function (von Ehrenstein et al 2007), skin lesions (Haque et al 2003;McDonald et al 2007; Kadono et al 2002), skin cancers (Karagas et al 2001;Chen and Ahsan 2004), bladder cancer (Bates et al 2004) and lung cancer (Ferreccio et al 1998). Non-cancerous health effects of arsenic are commoner than cancerous health effects and lead to high burden of disease (Rahman et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for burden of disease of arsenic due to drinking groundwater is still very sparse and accumulating (Rahman et al 2009). Arsenic leads to non-cancerous (non-malignant) and cancerous (malignant) health effects including cardiovascular disease (National Research Council 2001;Lee et al 2005;Chen et al 2009;Rahman et al 2009), peripheral neuropathy , decreased intellectual function (von Ehrenstein et al 2007), skin lesions (Haque et al 2003;McDonald et al 2007; Kadono et al 2002), skin cancers (Karagas et al 2001;Chen and Ahsan 2004), bladder cancer (Bates et al 2004) and lung cancer (Ferreccio et al 1998). Non-cancerous health effects of arsenic are commoner than cancerous health effects and lead to high burden of disease (Rahman et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nath et al [152] reported similar findings in their study population of Baruipur, South 24 Parganas district, West Bengal. Medical screening in the Bangladesh region [153] showed that most of the study populations were affected by keratosis and melanosis, whereas a few subjects were affected by chronic bronchitis and whole-body infection. In the West Bengal region, the individuals studied exhibited a full range of arsenical skin lesions, including hyperkeratosis, Bowen's disease (suspected), and non-healing ulcers (suspected cancer) [15,23,154].…”
Section: Bangladesh and West Bengal (India)mentioning
confidence: 99%
“…Arsenical hyperkeratosis appears predominantly on the palms and soles, and it has been found that keratosis on the soles is the most sensitive marker for the detection of arsenicosis at an early stage 38 . Keratoses are graded as mild, [Fig-4] moderate, or severe depending on the extent and severity 15 .…”
Section: Keratosismentioning
confidence: 99%